2004
DOI: 10.1038/ng1339
|View full text |Cite
|
Sign up to set email alerts
|

Functional variants of OCTN cation transporter genes are associated with Crohn disease

Abstract: Crohn disease is a chronic, inflammatory disease of the gastrointestinal tract. A locus of ∼250 kb at 5q31 (IBD5) 1,2 was previously associated with susceptibility to Crohn disease, as indicated by increased prevalence of a risk haplotype of 11 single-nucleotide polymorphisms 3 among individuals with Crohn disease, but the pathogenic lesion in the region has not yet been identified. We report here that two variants in the organic cation transporter cluster at 5q31 (a missense substitution in SLC22A4 and a G→C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
584
13
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 716 publications
(631 citation statements)
references
References 25 publications
23
584
13
11
Order By: Relevance
“…Some studies have reported that OCTN1 is capable of mediating carnitine uptake [6], but we could not reproduce these results in our laboratory using cloned rat and human OCTN1 (unpublished data). ATB 0,+ is a low-affinity transporter for carnitine [47].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Some studies have reported that OCTN1 is capable of mediating carnitine uptake [6], but we could not reproduce these results in our laboratory using cloned rat and human OCTN1 (unpublished data). ATB 0,+ is a low-affinity transporter for carnitine [47].…”
Section: Discussionmentioning
confidence: 73%
“…These studies included diverse populations and originated from Canada [6,13,14], the UK [15][16][17][18], Germany [19], New Zealand [20], Spain [21], Italy [22,23], Belgium [24], Greece [25], Sweden [26] and Japan [27,28]. One Japanese and another Hungarian study with a small number of subjects found no association between OCTN 1&2 transporter polymorphisms and CD [28,29]; thus there could be ethnic differences in IBD5 locus mutations and propensity for Crohn's disease [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the aetiology of these diseases is not fully understood, there is strong support for a genetic component based on findings of familial aggregation, higher concordance in monozygotic twins and ethnic differences in disease prevalence. 1,2 To date, different genetic studies have shown several genes playing a relevant role in these diseases, including NOD2/CARD15, 3 DGL5, 4 SLC22A4 and SLC22A5, 5,6 TNFSF15, 7,8 NOD1/CARD4 7 and IL23R. 9,10 NOD2/CARD15 is likely to be the major genetic factor contributing to CD.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Genetic linkage studies in IBD provide a thorough proof for a genetic background, 12 and the first disease gene (NOD2 or CARD15) has been identified for CD. [13][14][15][16][17] Genome-wide linkage analyses in large patient cohorts of different ethnic backgrounds have defined IBD susceptibility loci located on chromosomes 3, 6, 7, 12 and 16. 12,18-20 Recently, mutations in the murine Anterior Gradient 2 (AGR2) gene have been associated with a spontaneous phenotype characterized by diarrhea and goblet cell dysfunction resembling pathological changes seen in human UC (European patent WO2004056858).…”
Section: Introductionmentioning
confidence: 99%